Affecting Factors Teacher Work Satisfaction - Safrijal; Rosmala Dewi; Darwin (Publisher Cv. Inara, 2020)
Abstract. This study aims to determine the factors that effect teacher job satisfaction. In obtaining the data, a quantitsative approach is used with an explanatory coreeelational design because it aims to describe and measure the degree of relationship between variables in causal modeling using part analysis. The results showed that:First, leadership has a direct effect on teacher job satisfaction with a path coefficient of 0.173. Second, self esteem has a direct effect on teacher job satisfaction with a path coefficient of 0.173.